Commonly used earthquake source models - Liu, Wenlong; Liu, Yucheng (Geologos, 2012)
Several important earthquake source models that have been extensively used in seismological research and earthquake prediction are presented and discussed. A new fault source model is used to explain the earthquake focal mechanism solution and tectonic stress field, which play a crucial role in earthquake initiation and preparation. The elastodynamic-dislocation theory is demonstrated which provides the theoretical background of most earthquake source models. Important earthquake source models reviewed here include the double-force-couple point-source model, the circular-shear dislocation model, the finite moving-source model, the Brune model, and the spherical explosive source model.